The Phenomenon of Saving Glut in the Banking Industry during the Covid-19 Pandemic - Lucky Nugroho; Ahmad Badawi; Nurul Hidayah; Yananto Mihadi Putra (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2021)
The main business of bank financial institutions is to mobilize funds in the community through their savings and loan products. During the Covid-19 Pandemic, where the spread of the virus was speedy and a health protocol policy that limited community mobility, all economic sectors experienced a slowdown. Therefore, this study aims to analyze trends in third-party funds (liquidity) and loans (distribution of funds) during the Covid-19 Pandemic. The method used is qualitative by using descriptive statistics, namely analyzing trends in liquidity and distribution of funds in the banking industry, both Islamic banks and conventional banks. Based on the results of this study, it is known that the banking industry during the Covid-19 Pandemic experienced excess liquidity while loan disbursement experienced a decline. Furthermore, Islamic banks and conventional banks during the Covid-19 Pandemic had higher liquidity growth compared to the period before the Covid-19 Pandemic. However, compared to the intermediation function between conventional banks and Islamic banks, the intermediation function of conventional banks (LDR) during the Covid-19 pandemic was still better than the intermediation function of Islamic banks (FDR)